Estilos de crianza y la socialización en los niños de cinco años de la institución educativa inicial N°517 Amazonas, Nauta 2022 - Curichimba Ahuanari, Lupe (2025)
The purpose of this research was to analyze the relationship between parenting styles and socialization in five-year-old children who attend the Initial Educational Institution No. 517 Amazonas, Nauta, in 2022. The study is relational and adopts a non-experimental design. The population was made up of 41 children and their respective parents, covering the entire sample. For data collection, interview and observation were used as techniques, while the questionnaire and observation guide were the instruments used. The validity of these instruments was determined by expert judgment. The results show that there is no significant relationship between parenting style and socialization in the children of the studied sample. The correlation coefficient is almost zero and the significance is very high (0.951), which concludes that any observed relationship is probably due to chance. Therefore, based on these data, the general hypothesis is rejected and the null hypothesis is accepted.